Asymmetric Synthesis of Derivatives of Alanine via Michael Addition Reaction and their Biological Study - Mkrtchyan, Anna F.; Tovmasyan, Anna S.; Paloyan, Ani M.; Sargsyan, Armen S.; Simonyan, Hayarpi M.; Sahakyan, Lusine Yu.; Petrosyan, Satenik Gh.; Hayriyan, Liana A.; Sargsyan, Tatev H. (Synlett, 2022)
Ni(II) complex of the Schiff base of the chiral auxiliary (S)-2-N-(N′-benzylprolyl)aminobenzophenone (BPB) and dehydroalanine as the initial complex in the addition reaction was investigated. The obtained four new derivatives of α-alanine were investigated as inhibitors of aldose reductase. Only one of them: (S)-2-amino-3-[(4-methylbenzyl)amino]propanoic acid showed activity. It becomes a reason for studying the patterns of biological activity of the structure of α-amino acids. The results of docking analysis indicated that (S)-2-amino-3-[(4-methylbenzyl)amino]propanoic acid demonstrated the ability to form bonds with different functional groups of the enzyme which let us assume that some amino acids of nonfunctional groups, such as Trp20 of ALR2, can play a key role in inhibitor–enzyme interactions.
Keywords: unnatural amino acids; asymmetric synthesis; Michael addition reaction; docking analysis; inhibitor; aldose reductase